Convergence of Mass Communication Theory in Intercultural Communicationin the Era of Digital Communication: Communication of Married Couples of Different Nationalities on Yanti Guixe Family YouTube - Miranti Nilasari; Andrik Purwasito; Sri Hastarjo (Journal of Social Interactions and Humanities, 2023)
Digital technology greatly supports the ease of communicating and searching for various information from various countries in the world which has an impact on building relationships between people, one of which is the marriage of a couple from different countries between an Indonesian woman and a Spanish man with different cultural backgrounds uploaded on the YouTube channel. The purpose of this study is to determine how communication between marital couples of different countries is viewed from intercultural communication through uploads on the YouTube channel. By using descriptive qualitative method with systematic literature review research from various relevant national and international journal sources, then analyzed using intercultural communication theory. The study’s findings indicate that the achievement of harmony and adaptation by couples from various cultural background and countries is inextricably linked to individual acceptance of their respective cultures.